Aldh1L1 is expressed by postnatal neural stem cells in vivo. Issue 9 (8th July 2013) - Foo, Lynette C.; Dougherty, Joseph D.
<x xml:space="preserve">Abstract</x> The metabolic enzyme for folate, Aldh1L1, has been shown to be expressed robustly in astrocytes of the brain. It is now well accepted that astrocytes in certain regions of the adult brain also serve as neural stem cells. Here, we examined whether Aldh1L1 is also expressed in postnatal neural stem cells. In vitro, cells in neural stem cell culture conditions have robust Aldh1L1 promoter activity. In vivo, in the adult brain, astroctyes in neurogenic regions express Aldh1L1 in a pattern consistent with inclusion in neural stem cells, and analysis of Aldh1L1+ cell transcriptome profiles from neurogenic regions reveal a robust enrichment of known regulators of neurogenesis. Genetic fate mapping with Aldh1L1 BAC Cre animals reveals adult‐born neuroblasts of the rostral migratory stream are derived from Aldh1L1 expressing cells, as are sporadic neurons in other regions of the brain. Combining these lines of evidence from transgenic animals, cell culture, transcriptome profiling, and fate mapping, we conclude that Aldh1L1 is also expressed in neural stem cells in the brain. These findings may influence the future design of experiments utilizing Aldh1L1 genetic tools, and also suggest existing Aldh1L1 bacTRAP mice may be of use for further experiments profiling neural stem cells in vivo.